The encyclopedia of human resource management. Volume three, Thematic essays - Benscoter, George M.; Rothwell, William J., 1951- (Hoboken : John Wiley & Sons, 2012)
The three volumes in The Encyclopedia of Human Resource Management offer a comprehensive review of the essential issues and most important information available on the topic. Each volume in the encyclopedia contains contributions from some of the most celebrated names in the field of human resource management (HRM) and addresses the myriad challenges faced by today's human resource professionals. Volume 1 puts the focus on the definition of terms and practices that are most relevant to today's human resource management (HRM) professionals. The contributors bring an up-to-date perspective of HRM.
Front Matter -- Leadership and Learning. Best Practices in Leadership Development / Curtis D Curry -- Applying Learning and Organization Development Principles to Specific Organizational Contexts / Shelda Debowski -- Improving the Customer Learning Experience with Web-Interactive Guides / Kaliym Islam -- Leadership is Going Global / Rainhart Lang, Irma Rybnikova -- Web 2.0 Applications in Corporate Training / MJ Hall, Manuel London -- High-Octane Leadership / Craig M McAllaster, Lisa Lobao Junkerman -- The Social Construction of Productive Organizations / Thomas J Yannuzzi -- Leadership Versatility / J Preston Yarborough, Michael A Beitler -- Strategy and Measurement. Aligning Stakeholder Goals in a Measurement Project / Boyce Byerly -- Strategic Business Partner Role / David W Jamieson, Sue Eklund, Bob Meekin -- Human Resource Metrics / Tracy H Porter, Sharon E Norris -- The Eight Ps of Healthy Workplace Design / Kimberly S Scott -- The Evolution of Human Resources. The HR Transition to Strategic Partner / John Sherlock -- Reorganization of HRM--Past, Present, and Future / Peter M Wald, Rainhart Lang -- Workplace Bullying / Sara Branch, Jane Murray, Sheryl Ramsay -- Myths and Realities in Human Capital Development / Scott Cody, Wendy Green, Doug Lynch -- Lost Wisdom, Lost ROI / Edwina R Haring -- The Role of HR in Fostering Innovation in Organizations / James M Higgins -- Overtime Addiction / Eric C Jackson, Peg Thoms -- The Convergence and Divergence of HRM across Nations / Rainhart Lang, Peter M Wald -- Closing Critical Skills Gaps / Pamela Loughner -- Employee Engagement and Corporate Social Responsibility (CSR) / Philip H Mirvis -- Human Resource Transformation / Dayle A Savage -- The Implications of Situational Strength for HRM / Reeshad Dalal, Rustin Meyer -- Contributors -- Name Index -- Subject Index.
Description based upon online resource; title from PDF title page (viewed March 11, 2020).
John Wiley and Sons
Keywords: Personnel management -- Encyclopedias; Personnel -- Direction; Personnel management; encyclopedias; Encyclopedias; Encyclopedias; 2